Acupuncture as a pain reduction strategy in adults and elderly: integrative literature review - Lamego, Fabio Ricardo Dutra (2022)
Population development, poor eating habits, and lack of physical exercise bring a low quality of life among the elderly population due to pain. The objective is to seek scientific evidence of pain reduction using systemic acupuncture in adult and elderly individuals. Methodology: an integrative literature review study of articles extracted from the Virtual Health Library (BVS) database, with indexers from Latin American and Caribbean Health Literature (LILACS), Medical Analysis (MEDLINE/Pubmed), and the Database of Nursing Data (BDENF), from the descriptors: “acupuncture therapy”, “acupuncture”, “pain”, “adults”, and “aged”. The PICO strategy has been used. However, it boils down to an IOP acronym because adults and the elderly are the populations (P), acupuncture therapy is the intervention (I), and the outcome is the pain reduction (O). Original articles, from national and international databases with free access, were included, in English, Spanish, and Portuguese, the time frame adopted was from 2016 to 2021; while editorials, opinions, experience reports, review articles, and duplicate articles have been excluded, Results: After reviewing titles an amount of 8 articles have been found that addressed the use of systemic acupuncture, all published in international journals, 7 of which were randomized clinical trials. There was an amount of research with the gold standard but with a high risk of bias, and, of the 8 articles, all presented positive results for the use of the systemic acupuncture technique in the treatment of pain.